Ultrasonic Studies of Zirconium(IV) Soaps in Mixed Solvents - Varma, R.P.; Goel, H.; Singh, H.; Sharma, R.K. (Asian Journal of Chemistry, 2010)
Several acoustic parameters e.g. the adiabatic compressibility, intermolecularfree length, acoustic impedance, molar sound velocity, molarsound compressibility and solvation number of soaps intetrachloromethane, toluene and xylene were calculated at 35 and 45°C inpresence of 20% and 40% methanol. The results obtained provided importantinformation about the structural change of the soaps.